Pareto, Mosca, Michels, and the Advent of Fascism - Barbieri, Giovanni (Italian Sociological Review, 2024)
This article focuses on the attitudes of the classical elitists towards the advent of fascism, as elite theory represented one of the main reference points for many fascist thinkers. Born between 1848 and 1876, Gaetano Mosca, Vilfredo Pareto, and Roberto Michels had the opportunity to witness and evaluate the phenomenon of fascism firsthand. While all three scholars shared a deep fascination with fascism and its leader, there are several noteworthy differences in their thought, primarily due to their diverging intellectual journeys. The murder of Giacomo Matteotti in 1924 led Mosca to adopt a critical and oppositional position towards fascism and Mussolini, while Pareto died in 1923 and, thus, was unable to witness fascism’s transformation into a totalitarian regime. Nevertheless, one could argue that Pareto, who cautioned against governmental overreach and the suppression of freedoms and advocated for the preservation of parliament, would have disapproved of such a regime. Michels, on the other hand, embraced fascism with conviction and fervour.